Sistematización de cuidados de enfermería postquirúrgicos en mastectomías en mujeres jóvenes - Alcaciega Toapanta, Daisy Viviana (2026)
Mastectomy as a treatment for breast cancer causes multiple physical and emotional changes that require comprehensive care from nursing staff. The objective of this research was to systematize post-surgical nursing care in young women who have undergone mastectomy. The methodology used was a systematic review with a qualitative, descriptive approach. The PRISMA criteria were applied in the search for articles in PubMed, Google Scholar, and other databases, selecting 20 scientific articles published between 2020 and 2025. The findings identified actions such as emotional support, complementary therapies, pain management, drainage monitoring, and rehabilitation. Three phases of intervention were identified: preoperative, patient reception in the operating room, and postoperative. In high-pressure surgical contexts, care focused more on clinical tasks than on therapeutic communication. Strategies such as hygiene education, the use of pain scales, and support in bodily adaptation were applied. It was concluded that post-mastectomy care from nurses should be comprehensive, humanized, and based on individualized plans. Coordinated clinical and emotional interventions strengthen the professional role and promote more effective recovery in young women.